Antiplasmodial Compounds from Millettia Dura - Buyinza, Daniel; Derese, Solomon; Ndakala, Albert (Kabale University Interdisciplinary Research Journal, 2022)
Malaria still poses a big challenge to the health care of many tropical countries. The plasmodium resistance to the conventional drugs is the major hitch in its treatment. Higher plants have produced single line antimalarials and given important lead molecules. On this basis, flavonoids isolated from millettia dura by chromatographic techniques were screened againest W2 and D6 strains of plasmoduim falcipalum. Both, the crude and pure compounds tested showed mild activities against the test organisms. The crude extract of the stem bark had the highest respective activity of 63.7±8.6 and 46.1±4.5 μg/ml against W2 and D6. Of the pure compounds, milletosin was active towards both W2 and D6 with a respective IC50s of 87.9±8.9 and 66.70±30.3 μg/ml. Synergistic effect might have contributed to the relative high activity of the crude than the pure compounds. Basing on the structure activity relationship of the tested compounds, suitable structural modification could be ideal to enhance the antiplasmodial activity.
Keywords: Malaria, Antiplasmodial, Millettia dura, Higher-plants and antimalarial-resistance